Comprehensive identification of glycated peptides and their glycation motifs in plasma and erythrocytes of control and diabetic subjects - Zhang, Qibin; Monroe, Matthew E; Schepmoes, Athena A; Clauss, Therese R W; Gritsenko, Marina A; Meng, Da; Petyuk, Vladislav A; Smith, Richard D; Metz, Thomas O (Journal of proteome research, 2011)
Nonenzymatic glycation of proteins sets the stage for formation of advanced glycation end-products and development of chronic complications of diabetes. In this report, we extended our previous methods on proteomics analysis of glycated proteins to comprehensively identify glycated proteins in control and diabetic human plasma and erythrocytes. Using immunodepletion, enrichment, and fractionation strategies, we identified 7749 unique glycated peptides, corresponding to 3742 unique glycated proteins. Semiquantitative comparisons showed that glycation levels of a number of proteins were significantly increased in diabetes and that erythrocyte proteins were more extensively glycated than plasma proteins. A glycation motif analysis revealed that some amino acids were favored more than others in the protein primary structures in the vicinity of the glycation sites in both sample types. The glycated peptides and corresponding proteins reported here provide a foundation for potential identification of novel markers for diabetes, hyperglycemia, and diabetic complications in future studies.